Development of rice starch-fish gelatin edible films - Ahangari, Rozhin (2015)
Edible films of protein or carbohydrate have overall suitable mechanical properties but generally exhibit poor barrier properties. The use of a biopolymer like starch can be an interesting because this polymer is relatively cheap, abundant, biodegradable, and edible. The aim of this study was to incorporate fish gelatin and tannic acid (TA) into rice starch based edible films and investigate barrier, physicochemical and antimicrobial inhibition properties towards Escherichia coli, Listeria monocytogenes, Salmonella typhimurium, and Bacillus cereus by disc diffusion test in 25 and 4 oC. Film forming solutions of different concentrations of rice starch to fish gelatin (0 to 4 %) were prepared. The best film (fish gelatin: 1 %) containing sorbitol was incorporated with different concentration of TA (0.15, 0.3, 0.45, and 0.6 %) in acidic and alkaline pH. Film containing 0.45 % TA was used to wrap sausage in order to extend shelf life in chilled storage (4 oC) in compare with industrial package (LDPE) as a control. The addition of fish gelatin has a significant effect (p<0.05), resulting in lower tensile strength (TS), higher elongation at the break (EAB), water vapor permeability (WVP), oxygen permeability (PO2), and film solubility (FS), but made films slightly darker than rice starch edible film (control). The barrier properties of incorporated TA films were found to improve significantly (p<0.05) as compared to the non-treated. The addition of TA increased TS (10.83-62.68 MPa), decreased the permeability values, solubility and EAB (4.44 to 1.02 g.mm.m-2.day-1.KPa-1), (0.136 to 0.0025 %), and (27.97 to 16.82 %), respectively. The possible interactions between the two main components were evaluated by X-ray diffractometer (XRD) and Fourier-transform infrared spectroscopy (FTIR). The amide I and II band the most useful peak of the secondary structure of fish gelatin molecule shifted from 1534.54 to 1647.3 cm-1 in the edible films. In the TA incorporated films the characteristic peak of starch at 1536 cm-1 shifted to 1427 cm-1 and the amide peak of fish gelatin at 1642–1646 cm-1 indicating interaction between the amide groups and hydroxyl groups (-OH) of starch, fish gelatin, and TA. An amorphous state was observed in the film instead of the crystalline structure of starch granule, indicating molecular miscibility. The microstructure of the film showed smoother surfaces with decreasing fish gelatin, while increasing the TA content made the film more compact due to the networking introduced by tannic acid as observed in SEM. The comparison of inhibition zone was E. coli>L. monocytogenes>S. typhimurium> B. cereus with the increase of TA concentration. E. coli was more sensitive to the TA than L. monocytogenes, S. typhimurium, and B. cereus. The inhibition zoon in L. monocytogenes, S. typhimurium, and B. cereus in lower concentration of TA and control was not significant. However, in higher concentration of TA, there is no significant difference between inhibition zone of S. typhimurium and B. cereus either in room or in chilled storage. All sausages became drier than commercial wrapped sausages (MC: 69.97-27.55 %) and in relation to water activity; the average initial values were 0.950 and decreased to 0.850 and 0.920 during 4-week storage in sample and control, respectively. The sausages became more reddish (a value: 17.79-23.66) during chilled storage. As water activity decreased significantly (p<0.05), the total count decreased during storage (from 4.82 to 4.15 CFU/g in sample). The thiobarbituric acid reactive substances increased (1.90-4.06 μmol MA equivalent/per μmol PL) as well as control (1.90-5.24 μmol MA equivalent/per μmol PL), however; as compared to control there is lower TBARS after week 2. These results indicate that antimicrobial packaging with the inclusion of tannic acid as a natural antimicrobial could be considered as an effective technique to extend shelf life to 30 days in compare with control ≤ 2 weeks in 4 oC.